Perspectives on Aging Vestibular Function - Anson, Eric; Jeka, John (Frontiers in Neurology, 2016)
Much is known about age related anatomical changes in the vestibular system. Knowledge regarding how vestibular anatomical changes impact behavior for older adults continues to grow, in line with advancements in diagnostic testing. However, despite advancements in clinical diagnostics, much remains unknown about the functional impact that an aging vestibular system has on daily life activities like standing and walking. Modern diagnostic tests are very good at characterizing neural activity of the isolated vestibular system, but the tests themselves are artificial and do not reflect the multi-sensory aspects of natural human behavior. Also, the majority of clinical diagnostic tests are passively applied because active behavior can enhance performance. In this perspective paper we review anatomical and behavioral changes associated with an aging vestibular system and highlight several areas where a more functionally relevant perspective can be taken. For postural control, a multi-sensory perturbation approach could be used to bring balance rehabilitation into the arena of precision medicine. For walking and complex gaze stability, this may result in less physiologically specific impairments, but the trade-off would be a greater understanding of how the aging vestibular system truly impacts the daily life of older adults.